STRUKTUR ORGANISASI BUMN DAN IMPLEMENTASI GOOD CORPORATE GOVERNANCE: PENGAWASAN DAN PERAN STRATEGIS MENTERI, DIREKSI, DEWAN KOMISARIS, SERTA DEWAN PENGAWAS DALAM MENJAMIN AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN PERUSAHAAN NEGARA - Gunawan Widjaja (INTELIGENSIA MEDIA, 2025)
This study aims to analyse the organisational structure of State-Owned Enterprises (SOEs) and the implementation of Good Corporate Governance (GCG) in the context of supervision and the strategic roles of Ministers, Directors, Boards of Commissioners, and Supervisory Boards in ensuring the accountability and transparency of state-owned enterprise management. This study was motivated by the need for more efficient and professional governance, given the complexity of SOEs' functions as business entities and agents of national development. The research was conducted using a descriptive qualitative approach through a literature review method that examined various laws and regulations, policy documents, institutional reports, and relevant previous research results. The analysis was conducted using content analysis techniques to identify the conceptual relationship between the institutional structure of SOEs and the effectiveness of the implementation of GCG principles. The results of the study show that the effectiveness of SOE governance is greatly influenced by the clarity of institutional relations and the division of functions between key organs. The Minister of SOEs, as the government representative, plays a role in determining strategic policy directions and providing macro-level guidance, while the Board of Directors is responsible for operational management. The Board of Commissioners and the Supervisory Board serve to ensure a balance of authority through a system of checks and balances that strengthens accountability. However, in practice, the implementation of GCG still faces challenges in the form of overlapping authorities, weak supervisory independence, and political influence in the process of determining policies and managerial positions. This study emphasises that improving institutional structures, strengthening a culture of integrity, and consistently applying the principles of transparency and accountability are key to the successful implementation of GCG in SOEs. By strengthening inter-agency coordination, clarifying oversight mechanisms, and applying meritocracy in human resource management, SOEs can become models of efficient, clean, and competitive public corporate governance.